2013
DOI: 10.1093/neuonc/not051
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in telomerase-related genes are associated with an older age at diagnosis in glioma patients: evidence for distinct pathways of gliomagenesis

Abstract: Carrying a greater number of risk alleles might be expected to decrease age at diagnosis. However, glioma susceptibility conferred by variation in telomerase-related genes did not follow this pattern. This supports the hypothesis that telomerase-related mechanisms of telomere maintenance are more associated with gliomas that develop later in life than those utilizing telomerase-independent mechanisms (ie, alternative lengthening of telomeres).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 27 publications
2
52
1
Order By: Relevance
“…Gliomas account for approximately 80% of central nervous system malignant tumors and have a very poor prognosis (Schoemaker et al, 2010;Walsh et al, 2013b). Although the etiology of gliomas remains unclear, exposure to ionizing radiation has been identified as the only established risk factor (Little et al, 1998;Neglia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliomas account for approximately 80% of central nervous system malignant tumors and have a very poor prognosis (Schoemaker et al, 2010;Walsh et al, 2013b). Although the etiology of gliomas remains unclear, exposure to ionizing radiation has been identified as the only established risk factor (Little et al, 1998;Neglia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The gene polymorphisms increased or decreased glioma sensibility by regulating the proliferation and apoptosis of cells (Das et al, 2013;Liang et al, 2013). (Das et al, 2013;Li et al, 2013b) (Shete et al, 2009;Wrensch et al, 2009;Jin et al, 2013;Li et al, 2013;Walcott et al, 2013;Walsh et al, 2013a;Walsh et al, 2013b). Several research groups have reported associations between the rs6010620 single nucleotide polymorphism (SNP) and glioma risk.…”
Section: Introductionmentioning
confidence: 99%
“…The CCDC26 gene locus was strongly associated with glioma through five SNPs including rs4295627, rs16904140, rs6470745, rs891835, and rs10464870 [39][40][41][42] . Another, higher-resolution GWAS revealed the strongest association in the CCDC26 locus: rs55705857 with PBT [32,43] . A specific nucleotide in a CCDC26 SNP is a risk factor in low-grade (I-II) glioma, but not necessarily in high grade (III-IV) glioma cases [44] .…”
Section: Ccdc26 In Gliomamentioning
confidence: 99%
“…Previous large number of studies revealed that several candidate risk genetic variants of genes may associate with glioma, including 5p15.33 (rs2736100, TERT), 8q24.21 (rs4295627, CCDC26), 9p21.3 (rs4977756, CDKN2A-CDKN2B), 11q23.3 (rs498872, PHLDB1), and 20q13.33 (rs6010620, RTEL1) ( Shete et al, 2009;Schoemaker et al, 2010;Safaeian et al, 2013). In addition, other studies also indicated that the rs6010620 polymorphism in regulator of telomere elongation helicase1 (RTEL1) gene was associated with the risk of glioma (Chen et al, 2011;Li et al, 2013a;Walsh et al, 2013 gene named rs6010620 which locate at intron 12. RTEL1 is a DNA helicase.…”
Section: Introductionmentioning
confidence: 98%
“…Glioma are the most common adults tumors of the central nervous system (CNS), accounting for a majority (80%) of glioblastoma (Dolecek et al, 2012;Walsh et al, 2013). Although with optimal treatment, glioma have high mortality and morbidity, and median survival is just about 12-15 months (Ahmed et al, 2014).…”
Section: Introductionmentioning
confidence: 99%